Targeting Synthetic Advances in Extended Phenanthrene and Phenanthroline Systems - CONWAY-KENNY, ROBERT (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
The work herein describes the synthesis of a number of extended phenanthrene and phenanthroline systems as ligands, their Ru(II) and Ir(III) metal complexes, nitrogen-substituted graphene nanoribbons (N-GNRs), and as compounds potentially suitable for use as emitting layers in organic light emitting diodes (OLEDs). Extended 1,10-phenanthroline systems are generated for use as ligands, two containing quinone moieties, and one with inclusion of a central pyridazine ring. The generation of ?PhenBlue? is described, a phenanthroline-cyclopentadienone which is a structural analogue of tetracyclone. The development of a low temperature method towards its generation is detailed. The synthesis of Ru(II) and Ir(III) complexes from those ligands discussed is also detailed. Ru(II) complexes bearing bpy or phen ancillary ligands are generated using those ligands containing a quinone moiety. Ru(II) and Ir(III) complexes bearing bpy or ppy ancillary ligands respectively, are generated of the other two ligands. The first phenanthrene-pyridazine precursor suitable for the generation of pyridazine-substituted N-GNRs was designed and synthesised. The successful deposition of the dibrominated precursor to Au(111) surface was achieved. On-surface polymerisation was initiated thermally, with Scanning Tunneling Microscopy (STM) studies used to reveal the self-assembly of a packed structure of polymer chains. Thermogravimetric analysis (TGA) indicated thermal stability to 380 ?C, yet STM studies of a second annealing step revealed the failure of the polymer chains to undergo the desired cyclodehydrogenation step in the formation of the desired N-GNR. A phenanthrene-pyridazine ?acceptor? compound, and an ethynylpyrene ?donor-acceptor-donor? compound were generated, and investigated towards thermally activated delayed fluorescence (TADF) behaviour through solvatochromism and degassing studies. Both reveal intra-charge transfer (ICT) behaviour, demonstrating the successful access to the triplet state of the donor-acceptor-donor compound.
APPROVED
Keywords: phenanthrene; phenanthroline; graphene; nanoribbon; transition metal complex; tadf; pyridazine; Ru(II); Ir(III); quinone